Social Networking in Educational Settings: Between Instrumental Benefits and the Construction of Shared Meanings - Mrzlikar, Ajda; Zidar, Petra; Meško, Maja (Celovita pot izobraževanja: Od ideje do mreženja, 2026)
Social networking represents an important yet often overlooked dimension of professional educational events. The aim of this study was to examine how social interactions at professional events contribute to the development of professional relationships, sense of belonging, professional identity, and social capital among participants. Special attention was given to the role of informal interactions, organizational practices, and the relationship between physical and digital forms of networking. The study employed a mixed-methods approach. The findings suggest that participants do not perceive professional events merely as spaces for knowledge transfer, but also as important environments of professional socialization and community building. Networking was primarily associated with access to information, professional support, sense of acceptance, and the development of professional identity. Informal interactions played a significant role in establishing more durable and trust-based professional relationships. The results contribute to a broader understanding of professional educational events as social environments in which professional communities, belonging, and long-term social ties are formed alongside formal learning processes. Furthermore, the study highlights the importance of organizational practices that support more inclusive and accessible forms of professional networking.